1998
DOI: 10.1001/archinte.158.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a Practical Screening Instrument to Identify Patients at Risk for Diabetic Foot Ulceration

Abstract: The early detection of peripheral neuropathy or loss of "protective sensation" is paramount to instituting a structured treatment plan to prevent lower extremity amputation. The results of our study suggest that all 3 sensory perception testing instruments are sensitive in identifying patients at risk for ulceration. Combining modalities appears to increase specificity with very little or no diminution in sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
195
2
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 367 publications
(211 citation statements)
references
References 29 publications
1
195
2
9
Order By: Relevance
“…Monofilaments, sometimes known as Semmes-Weinstein monofilaments, were originally used to diagnose sensory loss in leprosy (21). Many prospective studies have confirmed that loss of pressure sensation using the 10-g monofilament is highly predictive of subsequent ulceration (3,21,22). Screening for sensory loss with the 10-g monofilament is in widespread use across the world, and its efficacy in this regard has been confirmed in a number of trials, including the recent Seattle Diabetic Foot Study (4,21,23,24).…”
Section: Neurological Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Monofilaments, sometimes known as Semmes-Weinstein monofilaments, were originally used to diagnose sensory loss in leprosy (21). Many prospective studies have confirmed that loss of pressure sensation using the 10-g monofilament is highly predictive of subsequent ulceration (3,21,22). Screening for sensory loss with the 10-g monofilament is in widespread use across the world, and its efficacy in this regard has been confirmed in a number of trials, including the recent Seattle Diabetic Foot Study (4,21,23,24).…”
Section: Neurological Assessmentmentioning
confidence: 99%
“…This process should initially be demonstrated on a proximal site, and then the mean of three readings is taken over each hallux. A VPT Ͼ25 V is regarded as abnormal and has been shown to be strongly predictive of subsequent foot ulceration (15,22).…”
Section: Neurological Assessmentmentioning
confidence: 99%
“…The 10-g SW-MF is tested on the plantar surface of the hallux and centrally at the heel. The ability to sense the SW-MF correctly in six trials at both locations is defined as normal; the inability to sense the SW-MF correctly in one of six trials is defined as mildly disturbed (score 1 point), and the inability to sense the SW-MF correctly more than one time is defined as disturbed and scores 2 points (11,12).…”
Section: Ndf/cbo Guidelinesmentioning
confidence: 99%
“…Experiência do Reino Unido revelou que o LPV, a partir de um nível de 25 volts, esteve associado a aumento no risco de úlcera, o que não ocorreu quando percebido com 15 volts ou menos (9). Outros estudos confirmaram o ponto de corte do LPV ≥ 25 volt como preditivo para ulceração do pé (10,11). Cada aumento de 1 volt da LPV no nível basal de percepção do indivíduo associou-se a aumento de 5,6% no risco de úlcera (12).…”
Section: Introductionunclassified